Simultaneous retrieval of T(p) and CO2 VMR from two-channel non-LTE limb radiances and application to daytime SABER/TIMED measurements. (August 2015) - Rezac, L.; Kutepov, A.; Russell, J.M.; Feofilov, A.G.; Yue, J.; Goldberg, R.A.
Abstract: The kinetic temperature, T k, and carbon dioxide, CO2 density, are key parameters that characterize the energetics and dynamics of the mesosphere and lower thermosphere (MLT) region. The Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) instrument on-board the Thermosphere-Ionosphere-Mesosphere-Energetics and Dynamics (TIMED) satellite has been providing global, simultaneous measurements of limb radiance in 10 spectral channels continuously since late January 2002. In this paper we (1) present a methodology for a self-consistent simultaneous retrieval of temperature/pressure, T k ( p ), and CO2 volume mixing ratio (VMR) from the broadband infrared limb measurements in the 15 and 4.3 μ m channels, and (2) qualitatively describe the first results on the CO2 VMR and T k obtained from application of this technique to the SABER 15 and 4.3 μ m channels, including issues, which demand additional constraints to be applied. The self-consistent two-channel retrieval architecture updates parameters at all altitudes simultaneously, and it is built upon iterative switching between two retrieval modules, one for CO2 and one for T k . A detailed study of sensitivity, stability and convergence was carried out to validate the algorithm. The T k /CO2 VMR distribution can be reliably retrieved without biases connected with this non-linear inverse problem starting with an initial guess as far as ±20% of CO2 VMR and ±15 K from the solution (as global shift, or somewhat larger if only local deviations are considered). In polar summer toward high latitudes the retrieved CO2 VMR profile shows a local peak around 90 km. We discuss details of this feature and show that: (a) it is not an algorithm artifact or instability, (b) additional a priori constraints are needed in order to obtain a physical profile and to remove this peak, and (c) several possibilities are explored as to uncover the real cause of this feature, but no firm conclusion can be reached at this time. This algorithm has been applied to all available daytime SABER measurements since 2002, and the first results of the mean CO2 VMR profiles and their distribution is discussed. In particular, the CO2 VMR profiles depart from a well mixed value at altitudes of 65–70 km during equinoxes at high and mid-latitudes, but in the summer hemisphere solstice period the SABER data is more consistent with a well mixed VMR conditions extend up to 87–90 km especially toward high latitudes. Abstract : Highlights: SABER 15 and 4.3 μ m channels are strongly coupled. The 2-channel algorithm is stable and self-consistent. Mean CO2 VMR profile appears to be well mixed up to 80–85 km. A CO2 90 km peak in polar summer is a persistent but unexplained feature. CO2 VMR decay depends on latitude and season.